Pemanfaatan Youtube Sebagai Media Pembelajaran Bahasa Jepang di SMAN 10 Malang Pada Masa Pandemi Covid-19 - Hermawan, Dhevi Amalia (Universitas Negeri Semarang, 2021)
SMAN 10 Malang began implementing learning from home activities since the issuance of a circular from the government regarding the implementation of education policies during the Covid-19 emergency. Japanese language learning which is one of the subjects at SMAN 10 Malang that is studied by students majoring in Language and Mathematics and Natural Sciences, is also carried out online. In meeting these challenges, Youtube media is used for Japanese language learning during home learning activities (BDR). This study aims to describe the use of Youtube in Japanese language class dan to determine how interest and student learning outcomes in Japanese language learning using Youtube media during BDR activities. The method used in this research is descriptive qualitative method with the process of collecting primary data through the results of student response questionnaires, as well as secondary data through the results of evaluation of student learning in Japanese language learning using Youtube media. The results of data analysis showed that students' interest in using Youtube media as a medium for learning Japanese language during BDR activities was in highest criteria. Moreover, the data has shown a satisfactory result in learning Japanese language through Youtube as a learning media.